2014
DOI: 10.11138/ccmbm/2014.11.2.132
|View full text |Cite
|
Sign up to set email alerts
|

Motorised mobility scooters; upper limb fractures in elderly novice users

Abstract: SummaryWe describe three upper limb injuries admitted in one year to our institution resulting from falls from motorised mobility scooters (MMS) where all three users were novices, using their MMS for less than 6 weeks. They sustained injuries in close proximity to their homes, necessitating admission to hospital. None had received any formal training before commencing use of their respective devices. Use of MMS devices increases independence in mobility, enhances quality of life, improves self-esteem, facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Similarly, a variety of accident rates have been reported for power wheelchair users (e.g., 5–18% of community dwelling users experience accidents each year [ 13 ]). To improve safety, scooter training has been recommended [ 14 ], which could include advanced skills such as navigating curbs and uneven surfaces, accessing public transit and elevators, and avoiding obstacles [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a variety of accident rates have been reported for power wheelchair users (e.g., 5–18% of community dwelling users experience accidents each year [ 13 ]). To improve safety, scooter training has been recommended [ 14 ], which could include advanced skills such as navigating curbs and uneven surfaces, accessing public transit and elevators, and avoiding obstacles [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of accident rates was described [20][21][22][23]; however, it should also be noted that the definition of accident varied considerably. On the low end, as part of a randomized controlled trial (RCT) by Hoenig et al [24], which involved data collection at 1 and 3 mo following scooter provision, an accident rate of 1.54 per person per year was reported.…”
Section: Research Topicsmentioning
confidence: 99%
“…Human factors are important to study because PMD drivers are a multifaceted subgroup of VRUs, which may contribute to an increased complexity in injury prevention strategies. Previous research has highlighted the importance of proper training in managing the PMD (Cassell and Clapperton 2006;Cordes et al 2018;Jancey et al 2013;Jannink et al 2008;Mortenson and Kim 2016;Mortenson et al 2017;Murphy et al 2014;Nitz 2008;Opalek et al 2009;Toosizadeh et al 2014). Because many PMD drivers experience difficulties maintaining an upright seated posture when subjected to external forces, seat belts and leg rests have been strongly recommended (Cooper et al 1998;Corfman et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Collision with objects on pathways or cars and stumbling on uneven surfaces or curbs represent other major reasons for injuries requiring hospital treatment. An Irish study describes upper limb fractures among 3 elderly novel MMS drivers (Murphy et al 2014). A literature review from New Zealand concluded that "operators of mobility scooters appear to be at significantly greater risk of being in an accident, and of being seriously or fatally injured in accidents, than other groups using the road corridor" (Newman 2015, p. 2).…”
Section: Introductionmentioning
confidence: 99%